2014
DOI: 10.1039/c3gc42189a
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced laccase stability through mediator partitioning into hydrophobic ionic liquids

Abstract: Partitioning mediators into water-immiscible ionic liquids protects laccase from inactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 59 publications
0
30
0
Order By: Relevance
“…Evidence for the existence of these mechanisms has been provided by examining the product pattern of non-phenolic lignin degradation, and measuring the intra-molecular kinetic isotope effects (Barreca et al, 2004). In the oxidation of non-phenolic LMCs, the efficiency of LMS was reported to be independent of the enzymes properties (Rosado et al, 2012). Oxidation of non-phenolic LMCs by laccase-ABTS was reported to occur via the electron transfer route (Bourbonnais et al, 1998).…”
Section: Biodegradation Of Lignin With Laccase-mediator Systemsmentioning
confidence: 99%
“…Evidence for the existence of these mechanisms has been provided by examining the product pattern of non-phenolic lignin degradation, and measuring the intra-molecular kinetic isotope effects (Barreca et al, 2004). In the oxidation of non-phenolic LMCs, the efficiency of LMS was reported to be independent of the enzymes properties (Rosado et al, 2012). Oxidation of non-phenolic LMCs by laccase-ABTS was reported to occur via the electron transfer route (Bourbonnais et al, 1998).…”
Section: Biodegradation Of Lignin With Laccase-mediator Systemsmentioning
confidence: 99%
“…6) the shift of the active site location in the overall structure of the enzyme. The use of redox mediators would seem to be a possible solution but involves certain problems such as the toxicity of some compounds in environmental processes and the deactivation effect on the 100 enzyme itself 11,42 . The use of redox mediators would seem to be a possible solution but involves certain problems such as the toxicity of some compounds in environmental processes and the deactivation effect on the 100 enzyme itself 11,42 .…”
Section: About Here]mentioning
confidence: 99%
“…The desired industrial purpose is often difficult to achieve using the 30 native form of the enzyme, and recent developments in enzyme engineering have revolutionized the development of commercially available enzymes for a better use as industrial catalysts 2, 7 . However, IL research has focused not only on replacing organic solvents in biocatalysis but also on identifying new possibilities in water-enzyme applications or for improving 45 the catalytic activity or/and stability inon the aqueous media 7,11 . trans-esterification reactions), their ability to increase the solubility of organic substrates and to 40 improve process performance increasing the enzyme activity, stability and selectivity, by ensuring a comfortable medium for the enzyme 8, 9,10 .…”
mentioning
confidence: 99%
“…This fact contributed to the maintenance of the activity of the laccase during the potential generation by the MFC since the enzyme has an oxido‐reductase activity and is needed to oxidise the ABTS to turn on the reduction of O 2 to H 2 O. In agreement with this, Rehmann et al . reported that using ABTS with hydrophobic IL (such as [NTf2] anion ILs) could contribute not only to enhancing laccase stability but also to protecting the enzyme against its redox mediator, such as ABTS.…”
Section: Resultsmentioning
confidence: 99%